Biodiversity of arbuscular mycorrhizal fungi and ecosystem function. Issue 4 (30th March 2018) - Powell, Jeff R.; Rillig, Matthias C.
Abstract : Contents   Summary 1059 I. Introduction: pathways of influence and pervasiveness of effects 1060 II. AM fungal richness effects on ecosystem functions 1062 III. Other dimensions of biodiversity 1062 IV. Back to basics – primary axes of niche differentiation by AM fungi 1066 V. Functional diversity of AM fungi – a role for biological stoichiometry? 1067 VI. Past, novel and future ecosystems 1068 VII. Opportunities and the way forward 1071   Acknowledgements 1072   References 1072 Summary: Arbuscular mycorrhizal (AM) fungi play important functional roles in ecosystems, including the uptake and transfer of nutrients, modification of the physical soil environment and alteration of plant interactions with other biota. Several studies have demonstrated the potential for variation in AM fungal diversity to also affect ecosystem functioning, mainly via effects on primary productivity. Diversity in these studies is usually characterized in terms of the number of species, unique evolutionary lineages or complementary mycorrhizal traits, as well as the ability of plants to discriminate among AM fungi in space and time. However, the emergent outcomes of these relationships are usually indirect, and thus context dependent, and difficult to predict with certainty. Here, we advocate a fungal‐centric view of AM fungal biodiversity–ecosystem function relationships that focuses on the direct and specific links between AM fungal fitness and consequences for their roles in ecosystems, especially highlighting functional diversity in hyphal resource economics. We conclude by arguing that an understanding of AM fungal functional diversity is fundamental to determine whether AM fungi have a role in the exploitation of marginal/novel environments (whether past, present or future) and highlight avenues for future research.